Restauraciones del pasado colonial en Argentina : proyectos de Mario J. Buschiazzo para la intervención de Monumentos Históricos Nacionales (1937-1947) - Herr, Carola Ingrid (2022)
This research, as part of heritage studies and aims to analyze the relations between heritage assessment and intervention in the context of the reassessment of colonial architecture during the foundational phase of the heritage field in Argentina (1937-1947). With that purpose, this work focuses in analyzing National Historic Monuments from the Colonial period located in the Center, Parana River Coastline and Northwest of Argentina and their interventions considering the projects developed by Mario J. Buschiazzo.\nTowards the end of 1930, Argentina began a systematic patrimonialization process that consolidated the colonial architecture as a reference of national identity. After a long process initiated, in the architectural field by the neocolonial movement debates, it was time to deal with preservation architecture. Once the political administrative structure to safeguard and protect heritage had been established through the creation of the National Commission of Museums, Monuments and Historical Sites (CNMMyLH in Spanish) the next mandatory step was to decide how to preserve the recently nominated historic monuments. Mario Buschiazzo a reference from history of colonial architecture in America, was in charge of designing the interventions for their re-assessment. Without local experience, with the colonial heritage in a heterogeneous conservation state and in an international context of dissociated criteria between theory and practice, the challenge was raised.\nBibliography points to the fact that Argentinian historical studies have assessed the colonial architecture based on a stylistic and synchronic approach, without considering the interventions that had taken place in these buildings. However, the current outlook of many of them is the result of the restorations implemented during the '40ties. Moreover, the approach that summarizes this period prevails in the iconic reconstruction examples from the Independence House in Tucuman and the Town Council from Buenos Aires.\nTaking this into account, the general purpose of this thesis is to increase the previous knowledge considering variability and new dimensions of analysis. Thus, the proposal is to deepen the analysis and to add specificity by studying the Town Council of Salta, the Posta of Sinsacate, the Uriburu House and the San Francisco Convent and Temple. These examples reflect restorations of monumental and modest architectural, with different valuation, acknowledgement and conservation state that allows to explore the relationship between the theoretical and the practical problems that converge at historic monuments during the foundational period of the CNMMyLH with an integral approach including the context, documental and technical-conservative dimensions.